Evaluation of cytotoxic and genotoxic effects of paclitaxel-loaded PLGA nanoparticles in neuroblastoma cells. (August 2021) - Bacanlı, Merve; Eşi̇m, Özgür; Erdoğan, Hakan; Sarper, Meral; Erdem, Onur; Özkan, Yalçın
Abstract: Neuroblastoma, a neoplasm of the sympathetic nervous system, is the second most common extracranial malignant tumor of childhood and the most common solid tumor of infancy. Paclitaxel (taxol), a diterpenoid pseudoalkaloid isolated from the shells of Taxus brevifolia, is the first taxane derivative used in the clinic for cancer treatment. Poly (lactic- co -glycolic acid) (PLGA) is one of the most successfully used biodegradable polymers for drug delivery which has a minimum systemic toxicity. This study aimed to evaluate the cytotoxicity and genotoxicity of paclitaxel nanoencapsulated with PLGA. Cytotoxic effects were determined by 3-(4, 5-Dimethylthiazol-2-yl)-2, 5-diphenyltetrazolium bromide (MTT) method and genotoxic effects were determined by single cell gel electrophoresis (Comet) method in human neuroblastoma cells (SH-SY5Y). According to our results, the viability of cells treated with concentrations higher than 10 nM of free paclitaxel and paclitaxel loaded PLGA nanoparticles for 48 and 72 h was found lower than 50%. Additionally, DNA damage increased with the increase of nanoparticle dose when the cells exposed to paclitaxel loaded PLGA nanoparticles for 24, 48 and 72 h. It can be concluded that PLGA nanoparticles can be considered as a biocompatible carrier system for drug delivery and might be promising agent against neuroblastoma.